Fire insulation of aluminum glazed partitions depending on the infill solution of framework profiles = Izolacyjność ogniowa aluminiowych przeszklonych ścian działowych w zależności od sposobu wypełnienia profili szkieletu - Sędłak, Bartłomiej; Roszkowski, Paweł; Sulik, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the main problems related to the fire resistance of aluminium glazed partitions. It discusses technical solutions used in partition systems with a specific fire resistance class, as well as a procedure and the general principles of classification of fire resistance for structures of this type.
Keywords: glazed partition; aluminium profile; insulation insert; fire resistance; fire integrity; fire insulation; ściana przeszklona; profile aluminiowe; wkład izolacyjny; odporność ogniowa; szczelność ogniowa; izolacyjność ogniowa; bezpieczeństwo pożarowe